2015
DOI: 10.3310/hta191010
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial of computerised cognitive behaviour therapy for the treatment of depression in primary care: the Randomised Evaluation of the Effectiveness and Acceptability of Computerised Therapy (REEACT) trial

Abstract: BackgroundComputerised cognitive behaviour therapy (cCBT) has been developed as an efficient form of therapy delivery with the potential to enhance access to psychological care. Independent research is needed which examines both the clinical effectiveness and cost-effectiveness of cCBT over the short and longer term.ObjectivesTo compare the clinical effectiveness and cost-effectiveness of cCBT as an adjunct to usual general practitioner (GP) care against usual GP care alone, for a free-to-use cCBT program (Moo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 76 publications
1
60
0
5
Order By: Relevance
“…Similar methods (large-scale screening of existing lists of potentially eligible patients) have underpinned a number of our successful large multicentre mental health trials [e.g. the Randomised Evaluation of the Effectiveness and Acceptability of Computerised Therapy (REEACT trial), 36 cost-effectiveness of collaborative care for depression in UK primary care trial (CADET) 37 ].…”
Section: Results Of the Internal Pilotmentioning
confidence: 99%
“…Similar methods (large-scale screening of existing lists of potentially eligible patients) have underpinned a number of our successful large multicentre mental health trials [e.g. the Randomised Evaluation of the Effectiveness and Acceptability of Computerised Therapy (REEACT trial), 36 cost-effectiveness of collaborative care for depression in UK primary care trial (CADET) 37 ].…”
Section: Results Of the Internal Pilotmentioning
confidence: 99%
“…with minimal professional support). 12 The REEACT-2 trial specifically tests the hypothesis that increasing the level of professional support offered alongside cCBT leads to a greater level of engagement with the computer technology and in turn leads to improved outcomes. The need for the REEACT-2 trial was highlighted by the negative results of the REEACT trial and the emergence of indirect evidence from systematic reviews which showed that meta-analyses of professionally supported cCBT demonstrated larger effect sizes than minimally supported cCBT.…”
Section: Discussionmentioning
confidence: 99%
“…12 The design of the REEACT trial was to compare the clinical effectiveness and cost-effectiveness of commercially developed cCBT (Beating the Blues; Ultrasis, London, UK) versus free-to-use cCBT (MoodGYM) versus usual GP care. The trial was pragmatic in design and recruited 691 participants in UK primary care.…”
Section: Evidence For Computerised Cognitive Behaviour Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…85 Although at the time that we planned this study NICE recommended computerised CBT packages for depression, 27,39,266 Kaltenthaler et al 85 have highlighted that all of the research published at the time of her review had been conducted on highly selected populations and more recent research based on the findings of the REEACT trial has questioned the efficacy of computerised CBT. 409 A qualitative study has highlighted the barriers to the use of computerised CBT experienced by many potentially suitable participants. 81 With regards to participants at raised CVD risk, earlier research had demonstrated the effectiveness of telehealth interventions for specific risk factors such as hypertension 150 and smoking cessation, 385,386 but our systematic review of trials of telehealth interventions aimed at reducing multiple risk factors to reduce overall CVD risk found no evidence of effectiveness.…”
Section: Depression and Cardiovascular Disease Risk As Exemplar Long-mentioning
confidence: 99%